Student Errors in Solving Higher Order Thinking Skills Problems: Bridge Context - Irfan, Muhammad; Widodo, Sri Adi; Sulistyowati, Fitria; Arif, Dery Fathurrahman; Syaifuddin, M Wahid (IndoMath: Indonesia Mathematics Education, 2022)
Errors in associating some knowledge result in students' mistakes in choosing strategies so that problems cannot be solved. In fact, the new curriculum in Indonesia requires students to be able to solve problems that require higher-order thinking skills. This study aims to describe how students process problems in solving bridge context problems. This research is qualitative research with case study method. This research was conducted in April 2022 with the research subject being a junior high school student in Yogyakarta, Indonesia. The instrument in this research is the problem of high order thinking (HOT) to measure problem solving ability. The instrument was designed based on the mathematics material that students had learned and compiled through five times Focus Group Discussion (FGD) by 3 mathematics lecturers. Data were collected using documentation and interviews then will be analyzed descriptively. Based on the results and discussion presented in the previous section, the authors collect three types of errors in solving problems made by students. The three types of errors are operational, conceptual, and principal errors.